Developing presentation skills: a handy guide for executives - Bhatia, R.L. (New Delhi Wheeler publishing, 1994)
The objective of this book is to make you an effective presenter. Possessing refined presentation skills has become a necessary and integral part of the executive personality. The book focuses on the importance of presentation in achieving success in business.
osc 29/01/2019
Loans
Keywords: Business presentations